Coordinated voltage control between wind power plant and shunt capacitors in weak distribution networks - Pachanapan,P. (2015)
© 2014 IEEE. The modern wind turbine, integrated with a power converter, can provide the decentralised voltage control similar to the power conditioner. The coordinated manner is implemented to manage the active and reactive powers support from wind power plant and the operating of shunt capacitor, to deal with either short- or long-term voltage variations in the weak distribution networks. The voltage control performances are demonstrated under various operating scenarios using the test system implemented in DIgSILENT PowerFactory.